How Internet use patterns affect scholastic performance of Moroccan high school students: a correlational study. - Garmah, Mohamed (Journal of North African Studies, 2023)
The aim of the current study is to explore the effects of Internet use patterns on the scholastic performance of Moroccan high school students. To answer its research questions, the study used a random-sample sampling method to select its subjects. 373 participants have been recruited and were asked to answer a questionnaire about their Internet use habits. Analyzing the obtained data, the study runs four Spearman's Rank Correlation tests to measure the strength and direction of the relationship between the variables using a two-tailed test of significance. The findings reveal a negative correlation between academic performance and time duration online. In terms of specific online activities, a negative correlation was found between academic performance and time spent on social networking websites, listening to music and playing games. However, a positive correlation was detected between using the Internet for academic purposes and good academic performance. This study has important implications for policymakers.